2021
DOI: 10.3390/pharmaceutics13020243
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Antinociceptive Properties of SJP-005 and Morphine in Rats

Abstract: SJP-005 (a combination of ketotifen and ibuprofen) is being developed as a potential treatment for pain and for opioid use disorder. It is therefore important to investigate the potential antinociceptive properties of SJP-005. Two studies were conducted to evaluate the potential effects of SJP-005 in rats. Study 1 applied the von Frey test to examine the antinociceptive effect of morphine with and without SJP-005 in adjuvant-induced hypersensitivity to tactile stimulation. In a double-blind, between-groups des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…30 A second study found that rats could withstand higher levels of painful stimuli when SJP-005 was co-administered, suggesting a possible opioid sparing effect. 31 A synergistic effect was demonstrated in a preclinical study demonstrating the effectiveness of another NSAID/antihistamine drug combination (SJP -002C, the combination of indomethacin and ketotifen) in inhibiting 2019 coronavirus replication. 32 Together, these studies suggest that NSAID/antihistamine drug combinations could be highly effective in conditions that are characterized by inflammatory responses of the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 A second study found that rats could withstand higher levels of painful stimuli when SJP-005 was co-administered, suggesting a possible opioid sparing effect. 31 A synergistic effect was demonstrated in a preclinical study demonstrating the effectiveness of another NSAID/antihistamine drug combination (SJP -002C, the combination of indomethacin and ketotifen) in inhibiting 2019 coronavirus replication. 32 Together, these studies suggest that NSAID/antihistamine drug combinations could be highly effective in conditions that are characterized by inflammatory responses of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Another NSAID/antihistamine drug combination (SJP – 005, the combination of ibuprofen and ketotifen) showed to be effective in significantly reducing the incidence and duration of discontinuation‐induced morphine withdrawal symptoms in rats, when treatment was initiated 2 days before morphine cessation 30 . A second study found that rats could withstand higher levels of painful stimuli when SJP‐005 was co‐administered, suggesting a possible opioid sparing effect 31 . A synergistic effect was demonstrated in a preclinical study demonstrating the effectiveness of another NSAID/antihistamine drug combination (SJP – 002C, the combination of indomethacin and ketotifen) in inhibiting 2019 coronavirus replication 32 .…”
Section: Discussionmentioning
confidence: 99%